Use of social media by health care professionals: is patients' privacy respected?. (25th November 2020) - Castrichini, M; Nuzzi, V; Sinagra, G; Cleland, J; Pellicori, P
Abstract: Background: The internet has a key role in sharing and expanding medical knowledge. Social networks offer health-care professionals the possibility to communicate, debate and learn from each other in real-time, thereby improving access to expertise and creating new knowledge. On Facebook, there are many groups that health-care professionals can join to discuss clinical cases. However, it is unknown if patient-privacy is respected and whether users are aware that they might be inadvertently involved in a criminal act for which they might be sued. Methods: We identified the most popular Facebook group for cardiologists, "ECHO BOARD REVIEW forum" that has more than 47, 000 users. We retrospectively evaluated all content posted by this group between February 6th and February 14th 2020. Information about the type of data posted, personal patient details, geographic location reported on images or videos, number of reactions and comments was collected. Privacy was considered fully violated when name and/or surname of the patient was identifiable. A comparison between the two cases (privacy preserved vs. privacy violated) was performed. Results: Of 53 posts evaluated, 50 (94%) were echocardiograms; the remaining three cases were of an electrocardiogram, a cardiac magnetic resonance video and a coronary angiogram. The patient's identity was revealed in seven cases (13%). Compared to cases where identity was concealed, those revealing the patient's identify were more likely to report other important personal details including date of birth (n=0 (0%) vs 2 (29%)), age (n=14 (30%) vs 5 (71%)) and sex (n=15 (33%) vs 6 (86%)). The country (n=46, 87%), city (n=39, 74%), and hospital (n=34, 64%) where the cases were being evaluated were also frequently disclosed. Most cases were from Asia (n=23, 43%) or Africa (n=17, 32%). Of the 7 cases in which privacy was fully violated, 43% were from Africa, 27% were from South America and 14% were from Asia. In the majority of cases, the author of the post was seeking diagnostic help (n=33), less frequently a diagnosis was already made by the author (n=17). The median (interquartile range) number of comments/post was 12 (5–23), and of likes/post was 21 (12- 37), with no significant difference between cases in which privacy was violated or not. Conclusion: Social media allows knowledge and expertise to be shared amongst health care professionals, but, alarmingly, violation of patient-confidentiality is common. In order to maintain patient-confidentiality and avoid breaking the law, strict rules should be applied to regulate the use of social media by health-care professionals. Funding Acknowledgement: Type of funding source: None